Information services for the visually handicapped : a study of user needs and library services in Singapore - Ng, Kirsten Eng Hong. (2009)
The objectives of this study were to conduct a questionnaire survey at the Singapore Association of the Visually Handicapped (SAVH) to determine the information needs and reading interests of persons with visual disabilities in Singapore; to elicit information about the services and collections provided by the Braille Library at the SAVH and the National Library for this user group; and to carry out a case study of the Special Needs Service at the State Library of New South Wales and present its services and technology for the visually handicapped.